Corruption In Digital Transformation: A Case Study Of The Impact Of Misappropriation Of Kominfo 4G BTS Project Funds On E-Government Governance In Indonesia - Naila Ahmad; Salwa Alfira; Clarissa Fortuna Paripurna; Fatkhuri (PT ARRUS Intelektual Indonesia, 2025)
Digital transformation through the implementation of E-Government aims to create efficient, transparent and accountable governance. However, in practice, this process is often hampered by corrupt practices that undermine the spirit of digitalization. This research examines the impact of the Ministry of Communication and Information Technology's misappropriation of funds for the 4G BTS development project, which caused state losses of Rp8.32 trillion, on E-Government governance in Indonesia. Using a descriptive qualitative approach and a case study method, this research will examine the impact of funding irregularities on the effectiveness of E-Government governance. The results show that corruption in the project not only hampered equitable access to digital infrastructure, but also undermined public trust and worsened the quality of digital services, especially in disadvantaged areas. The research also proposes preventive strategies that include strengthening digital surveillance, implementing anti-corruption technologies, and actively involving oversight institutions and the public in the procurement and implementation process of government digital projects. The findings are expected to serve as a policy reference in promoting government digital transformation with integrity and sustainability.